2013
DOI: 10.3109/19390211.2013.790332
|View full text |Cite
|
Sign up to set email alerts
|

A Short-Term Evaluation of the Relationship Between Plasma Ascorbic Acid Levels and Periodontal Disease in Systemically Healthy and Type 2 Diabetes Mellitus Subjects

Abstract: Plasma AAL is below the normal range in systemically healthy subjects with gingivitis and diabetics with periodontitis. Dietary AA supplementation with SRP improves the SBI in subjects with gingivitis and diabetics with periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 31 publications
2
62
3
5
Order By: Relevance
“…From these 46 potential relevant articles, 31 did not meet the criteria. Finally, 15 publications (7 cross-sectional studies [23][24][25][26][27][28][29], 2 case-control studies [30,31], 2 cohort studies [32,33]), and 4 RCTs [34][35][36][37]) were selected for systematic review, as shown in the flow chart ( Figure 1). Excluding the RCTs, 6 of the remaining 11 studies estimated vitamin C intake from dietary investigation and 6 studies measured blood vitamin C concentration.…”
Section: Literature Searches and Study Characteristicsmentioning
confidence: 99%
“…From these 46 potential relevant articles, 31 did not meet the criteria. Finally, 15 publications (7 cross-sectional studies [23][24][25][26][27][28][29], 2 case-control studies [30,31], 2 cohort studies [32,33]), and 4 RCTs [34][35][36][37]) were selected for systematic review, as shown in the flow chart ( Figure 1). Excluding the RCTs, 6 of the remaining 11 studies estimated vitamin C intake from dietary investigation and 6 studies measured blood vitamin C concentration.…”
Section: Literature Searches and Study Characteristicsmentioning
confidence: 99%
“…Akman et al [76] showed that the administration of vitamin C with or without alpha lipoic acid was associated with a significant decrease in serum myeloperoxidase levels, increased bone alkaline phosphatase levels, decreased alveolar bone resorption, and decreased RANKL-positive cell count. In individuals with chronic periodontitis, vitamin C intake in addition to nonsurgical periodontal treatment has been shown to decrease the gingival bleeding index levels [77]. Furthermore, it was reported that low serum levels of vitamin C and vitamin E may be risk factors for periodontal disease in elderly individuals [78].…”
Section: Vitamin Cmentioning
confidence: 99%
“…75 Kronik periodontitisli ve yeni tanı konmuş tip 2 Diabetes Mellitus'u olan bireylerde cerrahi olmayan periodontal tedaviye ek olarak C vitamini uygulamasının dişeti kanama indeksi değerlerini azalttığı ve çalışma başında düşük bulunan C vitamini düzeylerini arttırdığı gösterilmiştir. 76 Iwasaki ve ark. 'nın yaptığı çalışmada serum C ve E vitamini seviyelerinin periodontal hastalıkla ilişkisi longitudinal olarak incelenmiş; serum C ve E vitamini seviyelerinin düşük olmasının yaşlı bireylerde periodontal hastalık için risk faktörü olabileceği bildirilmiştir.…”
Section: B Karotenoi̇dlerunclassified